Temperature Humidity Control System and Fire Detection for Room Server Based Internet Of Things - Putra, I Gede Yudiana; Desnanjaya, I Gusti Made Ngurah; Adnyana, I Gede (Jurnal Galaksi, 2024)
The objective of this research is to develop an Internet of Things (IoT)-based temperature, humidity, and fire detection control system to monitor server rooms at INSTIKI. The research methodology employed involved the collection of primary data through interviews and observations, as well as secondary data through a comprehensive literature review. The system is implemented using a variety of electronic components, including the NodeMCU ESP32, the DHT22 sensor, the MQ2 gas sensor, the KY-026 flame sensor, the PZEM-004t sensor, the infrared emitter LED, the 20x4 I2C LCD, the buzzer, the 5V modules adapters, the step-down modules, and the SIM800l modules. The findings of this study illustrate that the devised system is effective in monitoring temperature, humidity, smoke, fire, and electricity in the INSTIKI server room. The monitoring data is displayed via a web platform, while warning notifications are sent via SMS and Telegram in the event of dangerous situations, resulting in a 100% success rate for notification delivery. The testing of the air conditioning temperature controls using SMS also achieved a 100% success rate. However, the efficacy of the IR Remote is contingent upon the distance and position of the Infrared Emitter LED in relation to the AC's receiver sensors, as well as the quality of the signal received by the GSM800l module.